Comparison Analisys of Financial Performance of Village Owned Business Entity (BUMDes) “Bina Mandiri” Jada Bahrin Village and Village Owned Business Entity (BUMDes) “Pagarwan” Pagarawan Village 2019-2021 Period - Wahyuni, Wahyuni; Nugroho, Ari Agung; Hamsani, Hamsani (Garuda Prestasi Nusantara Consulting, 2022)
This study aims to analyze and compare the financial performance of BUMDes